2016
DOI: 10.1002/ceat.201600243
|View full text |Cite
|
Sign up to set email alerts
|

Recycling and Oligomerization Activity of Ni/Al Catalyst in a Biphasic System with Ionic Liquids

Abstract: The catalyst decomposition in homogeneously catalyzed reactions is a very important factor that has been studied for the oligomerization of n-butenes in a system of two liquid phases. A highly active catalyst [NiCl 2 (PMe 3 ) 2 ] was investigated with an emphasis on the long-term catalyst activity using N-methylpyrrole as a buffer. The recycling experiments indicated that this catalyst is viable for five runs. Furthermore, introducing aluminum chloride or an ionic liquid in small concentrations led to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The oligomerization of 1-butene in N-methylpyrrole-buffered ionic liquid ([BMI][Cl]/AlCl 3 /NMP) was later studied in more details. 177,178 Systematic investigations of IL/NMP/Ni-(PMe 3 ) 2 Cl 2 ratios demonstrated that NMP and IL concentrations are critical parameters. The molar ratio of the IL to Nmethylpyrrole needs to be balanced at 1/10, since a high buffer concentration leads to catalyst blockage, whereas a low buffer concentration promotes the formation of higher oligomers.…”
Section: Liquid−liquid Biphasic Catalysis In Unconventional Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…The oligomerization of 1-butene in N-methylpyrrole-buffered ionic liquid ([BMI][Cl]/AlCl 3 /NMP) was later studied in more details. 177,178 Systematic investigations of IL/NMP/Ni-(PMe 3 ) 2 Cl 2 ratios demonstrated that NMP and IL concentrations are critical parameters. The molar ratio of the IL to Nmethylpyrrole needs to be balanced at 1/10, since a high buffer concentration leads to catalyst blockage, whereas a low buffer concentration promotes the formation of higher oligomers.…”
Section: Liquid−liquid Biphasic Catalysis In Unconventional Mediamentioning
confidence: 99%
“…Both activities and selectivities of homogeneous (PCy 3 ) 2 NiCl 2 -catalyzed propylene dimerization reactions with buffered AlCl 3 co-catalysts (Al/Ni=850, seem to correlate with this analysis. Catalyst precursor used for propylene dimerization in triphenylbismuth buffered Lewis acidic chloroaluminate ionic liquids The oligomerization of 1-butene in N-methylpyrrole-buffered ionic liquid ([BMI][Cl]/AlCl 3 /NMP) was later studied in more details 177,178. Systematic investigations of IL/NMP/Ni(PMe 3 ) 2 Cl 2 ratios demonstrated that NMP and IL concentrations are critical parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Simple synthesis, controlled acid strength, gentle reaction conditions and repeatability are all advantages of supported catalysts 19‐22 . The high cost of ionic liquid catalysts is a drawback 23‐25 . In consideration of the characteristics of the above catalysts, the authors believe that supported molecular sieve catalysts are of great significance in the study of the application of selective oligomerization of isobutene.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] The high cost of ionic liquid catalysts is a drawback. [23][24][25] In consideration of the characteristics of the above catalysts, the authors believe that supported molecular sieve catalysts are of great significance in the study of the application of selective oligomerization of isobutene. Due to the higher decomposition temperature of FeCl 3 , calcination after equal volume impregnation is more conducive to the generation of ⊍-Fe 2 O 3 with larger particle size, and FeCl 3 aqueous solution has strong acidity so that the catalyst can be acid-treated, and the pore diameter of the catalyst can be enlarged.…”
Section: Introductionmentioning
confidence: 99%